India's exports and export policies in the 1960s - Nayyar, Deepak (Cambridge : Cambridge University Press, 1976)
This volume x-rays India's exports and export policies in the 1960s. It is divided into three parts: general; empirical analysis-micro approach; policy analysis-macro economic view.
Includes bibliographical references and index.
lje 23/1/19
Loans
Keywords: Commerce; Commerce-India; Export marketing; India